Socio-cultural determinants of health-seeking behaviour on the Kenyan coast: a qualitative study - Abubakar, A; Van Baar, A; Fischer, R; Bomu, G; Gona, J; Newton, C (Public Library of Science, 2013)
Background Severe childhood illnesses present a major public health challenge for Africa, which is aggravated by a suboptimal response to the child's health problems with reference to the health-seeking behaviour of the parents or guardians. We examined the health-seeking behaviour of parents at the Kenyan coast because understanding impediments to optimal health-seeking behaviour could greatly contribute to reducing the impact of severe illness on children's growth and development. Methods and Results Health-seeking behaviour, and the factors influencing this behaviour, were examined in two traditional communities. We held in-depth interviews with 53 mothers, fathers and caregivers from two rural clinics at the Kenyan Coast. Biomedical medicine (from health facilities and purchased over the counter) was found to be the most popular first point of treatment. However, traditional healing still plays a salient role in the health care within these two communities. Traditional healers were consulted for various reasons: a) attribution of causation of ill-health to supernatural sources, b) chronic illness (inability of modern medicine to cure the problem) and c) as prevention against possible ill-health. In developing an explanatory model of decision-making, we observed that this was a complex process involving consultation at various levels, with elders, but also between both parents, depending on the perceived nature and chronicity of the illness. However, it was reported that fathers were the ultimate decision makers in relation to decisions concerning where the child would be taken for treatment. Conclusions Health systems need to see traditional healing as a complementary system in order to ensure adequate access to health care. Importantly, fathers also need to be addressed in intervention and education programs.